An Interactive Approach of Teaching and Learning Prerequisite Mathematics Course and Core Engineering Mathematics Course During COVID-19 Pandemic - Vojo George Fasinu (Interdisciplinary Journal of Education)
The emergence of COVID-19 brought up some concerns and changes in the approaches to the teaching and learning of some engineering related modules, particularly in South Africa. Therefore, the teaching of an electronics engineering course demands a balanced interactive approach, as requested by the curriculum. On this note, this paper reports the common approaches of teaching and learning mathematical modelling in antenna theory and design. It also discusses the perceived impact of interactive learning on modelling some mathematical skills in engineering education. It emphasizes the form of interaction that exists among students and lecturer, lecturer and students, and the whole class with the lecturer. The paper therefore reports the strategies of teaching and learning of mathematical modelling in Antenna Theory and Design (ATD), using the interactive methods, as suggested by the University during COVID-19 period. In view of this, the paper confirms that the adoption of an interactive teaching and learning method helps to increase students’ understanding when learning ATD. In achieving the goal of the study, a qualitative style of data collection was adopted, coupled with a thematic approach of discussion of the study. This gives room for the appropriate approach of teaching and learning of mathematical modelling, in ATD courses, during COVID-19 era in a university in South Africa.